Thermal degradation of defective high-surface-area UiO-66 in different gaseous environments. Issue 61 (3rd December 2021) - Athar, Muhammad; Rzepka, Przemyslaw; Thoeny, Debora; Ranocchiari, Marco; Anton van Bokhoven, Jeroen
Abstract : The crystallinity of the framework of UiO-66 with defects is lost upon heating at 250 °C, whereas the decomposition starts at ∼450 °C depending on the conditions. Tetragonal zirconia forms as a dominant decomposition product on heating up to 600 °C. Abstract : UiO-66 is a versatile zirconium-based MOF, which is thermally stable up to 500 °C. In the present work, the thermal degradation of UiO-66 with a high number of defects has been studied in inert, oxidative and reductive environments. A sample of UiO-66 with a high BET surface area of 1827 m 2 g −1 was prepared, which contains 2.3 missing linkers per hexa-zirconium node, as calculated by the thermogravimetric curve. The crystalline framework of this UiO-66 sample collapses at 250 °C, while thermal decomposition starts at 450 °C in the oxidative environment and at 500 °C in the reductive and inert environments. The BET surface area of the MOF is affected variably by heating under different gaseous conditions. Under inert conditions, porosity is maintained up to 711 m 2 g −1, which is quite high when compared to that under reductive (527 m 2 g −1 ) or oxidative (489 m 2 g −1 ) conditions. Upon complete thermal decomposition at 600 °C, the MOF produces predominantly tetragonal zirconia. TEM images of the thermally decomposed samples show that the shape of the original MOF crystal is maintained during the heating process in the inert and reductive environments, whereas under oxidative conditions, all of the carbon is burnt to carbon dioxide, leaving no carbon matrix as the support.